Long‐acting and extended‐release implant and nanoformulations with a synergistic antiretroviral two‐drug combination controls HIV‐1 infection in a humanized mouse model. Issue 1 (26th June 2021) - Beloor, Jagadish; Kudalkar, Shalley N.; Buzzelli, Gina; Yang, Fan; Mandl, Hanna K.; Rajashekar, Jyothi K.; Spasov, Krasimir A.; Jorgensen, William L.; Saltzman, W. Mark; Anderson, Karen S.; Kumar, Priti
Abstract: The HIV pandemic has affected over 38 million people worldwide with close to 26 million currently accessing antiretroviral therapy (ART). A major challenge in the long‐term treatment of HIV‐1 infection is nonadherence to ART. Long‐acting antiretroviral (LA‐ARV) formulations, that reduce dosing frequency to less than once a day, are an urgent need that could tackle the adherence issue. Here, we have developed two LA‐ART interventions, one an injectable nanoformulation, and the other, a removable implant, for the delivery of a synergistic two‐drug ARV combination comprising a pre‐clinical nonnucleoside reverse transcriptase inhibitor (NNRTI), Compound I, and the nucleoside reverse transcriptase inhibitor (NRTI), 4′‐ethynyl‐2‐fluoro‐2′‐deoxyadenosine. The nanoformulation is poly(lactide‐ co ‐glycolide)‐based and the implant is a copolymer of ω‐pentadecalactone and p‐ dioxanone, poly(PDL‐ co ‐DO), a novel class of biocompatible, biodegradable materials. Both the interventions, packaged independently with each ARV, released sustained levels of the drugs, maintaining plasma therapeutic indices for over a month, and suppressed viremia in HIV‐1‐infected humanized mice for up to 42 days with maintenance of CD4 + T cells. These data suggest promise in the use of these new drugs as LA‐ART formulations in subdermal implant and injectable mode.